Sequence and phylogenetic analysis of chicken reoviruses in China - Chu WEN; Qi ZHONG; Jia-dong ZHANG; Jian-shan LU; Li-xin ZHANG; Xi-min YUAN; Meng-hou GAN; Xue-peng CAI; Guo-zhong ZHANG (Journal of Integrative Agriculture, 2016)
Avian reovirus (ARV) has been responsible for many cases of chicken tenosynovitis in China in recent years, causing high morbidity among layer and broiler chickens. To study the degree of genetic divergence and evolution among ARVs, the full-length nucleotide sequences of the σC-encoding gene of eight ARV field isolates and the entire coding-region sequences of four isolates were determined and analyzed. The sequence analysis revealed that the eight σC-encoding genes shared 99.0–99.9% nucleotide sequence identity with each other and over 99% with the chicken reovirus reference strain S1133. However, the nucleotide sequences of the eight σC-encoding genes varied extensively from that of isolate AVS-B (GenBank accession no. FR694197), with only 55.5% identity. A sequence analysis of the whole ARV-coding region showed some nucleotide substitutions in the open reading frames encoding λA, λB, λC, μA, μB, μNS, σC, σA, σB, and σNS in the field strains. A phylogenetic analysis showed that all eight isolates clustered in group I with S1133, but that four field isolates shared less homology with strain S1133 than the others, indicating that they had been evolved in the field. We also studied the pathogenicity of two strains. No characteristic lesions were observed in vaccinated chickens, and no virus was detected in sampled tissues. However, an enzyme-linked immunosorbent assay revealed significant differences between the antibody responses of the inoculated groups and the negative controls. These results revealed that Chinese isolates shared the highest sequence homologies with S1133, grouped together in one cluster. Although the vaccination against ARV is used in farms, the pathogens still persist in Chinese poultry flocks.